2013
DOI: 10.1038/msb.2013.57
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial evolution of antibiotic hypersensitivity

Abstract: Understanding how adaptation to a given antibiotic increases the sensitivity to other antibiotics is of great medical importance for the understanding of evolutionary trade-offs. Here, the first experimental map of such collateral sensitivity is presented, along with insights into the underlying mechanisms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
379
3
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(407 citation statements)
references
References 48 publications
24
379
3
1
Order By: Relevance
“…This could have important clinical consequences, as unsuccessful antibiotic treatments might select for cross-tolerance and limit the efficacy of subsequent treatments with other antibiotics. It is also interesting to note how our observations differ from the results of recent work on the experimental evolution of aminoglycoside resistance (55). In this work, researchers describe how increased aminoglycoside resistance correlates with enhanced susceptibility to a whole range of other antibiotics, including ciprofloxacin, vancomycin, and ␤-lactams.…”
Section: Figcontrasting
confidence: 68%
“…This could have important clinical consequences, as unsuccessful antibiotic treatments might select for cross-tolerance and limit the efficacy of subsequent treatments with other antibiotics. It is also interesting to note how our observations differ from the results of recent work on the experimental evolution of aminoglycoside resistance (55). In this work, researchers describe how increased aminoglycoside resistance correlates with enhanced susceptibility to a whole range of other antibiotics, including ciprofloxacin, vancomycin, and ␤-lactams.…”
Section: Figcontrasting
confidence: 68%
“…Bacterial growth was monitored by measuring the optical density (OD 600 ) of the liquid cultures at a single time point. Preliminary experiments showed that a single reading of optical density after 18 h of incubation showed strong linear correlation with the area under the growth curve (a descriptor of overall inhibitory effect that covers the entire growth period) (21). Briefly, this was determined using parallel cultures of E. coli grown in ten 384-well microtiter plates under previously stated conditions.…”
Section: Methodsmentioning
confidence: 99%
“…The most Drug sequence influences evolution of resistance commonly mutated gene was fusA1, which encodes elongation factor G and was mutated in 11 different replicate lineages adapted to tobramycin. fusA1 has been observed to be mutated in clinical isolates of P. aeruginosa [39][40][41], as well as in adaptive evolution studies to aminoglycosides in P. aeruginosa [34] and E. coli [12,16,18]. Mutations in fusA1 may also contribute to altered intracellular (p)ppGpp levels, which may modulate virulence in P. aeruginosa [41].…”
Section: Genomic Mutations Of Adapted Lineagesmentioning
confidence: 99%
“…Recent studies have explored how adaptation to an antibiotic can cause bacteria to concurrently become more susceptible or more resistant to other drugs, an effect termed collateral sensitivity or collateral resistance [14,16,17]. Collateral sensitivities between drugs have been used to design drug cycling strategies and to explain the decreased rate of adaptation to certain antibiotics [12,14,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%